Uji Resistensi Colletotrichum sp. Asal Cabai Hiyung Terhadap Fungisida Berbahan Aktif Klorotalonil dan Mankozeb - Hajijah Hajijah; Mariana Mariana; M Indar Pramudi (www.ulm.ac.id, 2022)
The use of fungicides, one of which is the active ingredient chlorotalonil and mankozeb, if not used as recommended, can cause resistance to the fungus Colletotrichum sp. This study aims to determine the level of resistance Colletotrichum sp. origin of hiyung chili against fungicides with the active ingredients of chlorotalonil and mankozeb at certain concentrations. This study used the RAL method with a fungicide with the active ingredient chlorotalonyl 6 treatments and 4 replications so that 24 experimental units were obtained, the fungicide with the active ingredient mankozeb in 11 treatments and 3 replicates in order to obtain 33 experimental units. The test was carried out in vitro with the growth medium poisoning method. Observations were made by measuring the colony diameter of the fungus Colletotrichum sp, calculating the Relative Resistance Level (RRL) and then determining the resistance level. The results obtained in this study indicate that the fungicide with the active ingredient chlorotalonyl can increase the relative inhibition level of the fungus Colletotrichum sp. from Hiyung chili, but the fungus is categorized as highly resistant to fungicides with the active ingredient chlorotalonyl at the recommended concentration, as well as two levels below and two levels above the recommended concentration. The fungicide with the active ingredient mankozeb has a relatively high level of inhibition (99.44 %) so that the isolates of the fungus Colletotrichum sp. The origin of hiyung chili is in the category of very sensitive to fungicides with the active ingredient mankozeb at recommended concentrations of up to 10 times the recommended concentration.